2016
DOI: 10.1128/mcb.00345-16
|View full text |Cite
|
Sign up to set email alerts
|

Activated Transcription Factor 3 in Association with Histone Deacetylase 6 Negatively Regulates MicroRNA 199a2 Transcription by Chromatin Remodeling and Reduces Endothelin-1 Expression

Abstract: P lacenta growth factor (PlGF), an angiogenic growth factor of the vascular endothelial growth factor (VEGF) family, has pleiotropic and redundant roles in development but features prominently in various pathological conditions such as ischemia, angiogenesis, inflammation, atherosclerosis, preeclampsia, and diabetic wound healing (1-9). PlGF expression is induced by hypoxia, erythropoietin, and iron; PlGF effects are manifested via binding to its sole cognate receptor, VEGF receptor 1 (VEGFR-1) (10-13).Recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…ATF3 has been shown to play an important role in the pathophysiology of diseases, including cancer, immunity and sepsis (8082). Studies showed ATF3 binds to DNM3os promoter proximal cis-binding elements, located at −42/−35 nt and −816/−809 nt), as demonstrated by gain and loss of function of ATF3, DNM3os promoter-luciferase reporter assay and ChiP analysis (Figure 5)(79). Other studies have shown ATF3 can act either as a repressor or activator of transcription by recruitment of accessory proteins to the promoter element of genes (83).…”
Section: Pparα Agonists Augment Mir-199a2 and Reduce Hif-1a And Ementioning
confidence: 97%
See 4 more Smart Citations
“…ATF3 has been shown to play an important role in the pathophysiology of diseases, including cancer, immunity and sepsis (8082). Studies showed ATF3 binds to DNM3os promoter proximal cis-binding elements, located at −42/−35 nt and −816/−809 nt), as demonstrated by gain and loss of function of ATF3, DNM3os promoter-luciferase reporter assay and ChiP analysis (Figure 5)(79). Other studies have shown ATF3 can act either as a repressor or activator of transcription by recruitment of accessory proteins to the promoter element of genes (83).…”
Section: Pparα Agonists Augment Mir-199a2 and Reduce Hif-1a And Ementioning
confidence: 97%
“…PlGF treatment of cultured endothelial cells increased expression of activating transcription factor-3 (ATF3), a stress inducible gene (79). ATF3 has been shown to play an important role in the pathophysiology of diseases, including cancer, immunity and sepsis (8082).…”
Section: Pparα Agonists Augment Mir-199a2 and Reduce Hif-1a And Ementioning
confidence: 99%
See 3 more Smart Citations